Class-based multicast routing in interdomain scenarios - Nicolau, Maria João (2008)
DiffServ-like domains bring new challenges to quality of service (QoS) multicast routing simply by shifting the focus from individual flows into classes of flows. Packets are marked at edge routers and receive differentiated treatment according to the class and not the flow that they belong to. DiffServ therefore became adverse to multicast, as packet replication inside the domain may require classification and remarking functions not present in core nodes. At the interdomain level, no doubt multicast QoS complexity is increased by the interleaving of DiffServ and non-Diffserv domains, making it more difficult to address QoS multicast in an end-to-end perspective. In today’s real interconnection world, classes of service have no meaning in certain links of a full interdomain path. While the problem is not new, as already pointed out, there are no real efforts to bring multicast back to a class-of-service domain without compromising its model of operation. In this article, we present an innovative multicast QoS routing strategy, clearly designed for the new class-of-service paradigm. The solution is based upon the construction of multiple trees, one per class of service available, while still allowing receivers to shift for source-specific trees in its own class of service. The strategy is presented in a full end-to-end perspective. Intradomain trees use differentiated routing paths thus helping traffic differentiation. Intradomain receivers are allowed to shift from shared trees into an adequate class-of-service source tree. At interdomain level, each class-of-service interdomain tree branch is accomplished by means of an improved path probing strategy enabling for QoS path establishment. This paper presents this new strategy, and associated protocols, for constructing several multicast and directed distribution trees, one per class of service, within each multicast group. This new strategy and associated protocols are then simulated using NS-2 platform. Simulation results are analyzed and compared with other multicast routing solutions, both at intra- and interdomain levels.